2023
DOI: 10.3389/fcdhc.2023.1270028
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated coagulation system links to inflammation in diabetic kidney disease

Mengyun Xiao,
Donge Tang,
Shaodong Luan
et al.

Abstract: Diabetic kidney disease (DKD) is a significant contributor to end-stage renal disease worldwide. Despite extensive research, the exact mechanisms responsible for its development remain incompletely understood. Notably, patients with diabetes and impaired kidney function exhibit a hypercoagulable state characterized by elevated levels of coagulation molecules in their plasma. Recent studies propose that coagulation molecules such as thrombin, fibrinogen, and platelets are interconnected with the complement syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…Overexpression of PAI-1 is thought to occur due to the direct influence of insulin and proinsulin. Various studies conducted on diabetes mellitus sufferers have reported increased levels of various blood clotting factors that play a role in the intrinsic pathway (kallikrein, vWF, F VIII, FIX, F.XII), as well as those that play a role in the extrinsic pathway (TF and F.VII) (Xiao et al, 2023).…”
Section: D-dimer Value Parameter In Terms Of Patient Comorbidities Na...mentioning
confidence: 99%
“…Overexpression of PAI-1 is thought to occur due to the direct influence of insulin and proinsulin. Various studies conducted on diabetes mellitus sufferers have reported increased levels of various blood clotting factors that play a role in the intrinsic pathway (kallikrein, vWF, F VIII, FIX, F.XII), as well as those that play a role in the extrinsic pathway (TF and F.VII) (Xiao et al, 2023).…”
Section: D-dimer Value Parameter In Terms Of Patient Comorbidities Na...mentioning
confidence: 99%